Acts of Conscience: Christian Nonviolence and Modern American Democracy - Chernus, Ira (A journal of church and state, 2009)
Acts of Conscience is the most sophisticated scholarly study yet of America's Christian nonviolence movement from its rebirth during World War I to its greatest political triumph, the Civil Rights movement of the 1960s. Kosek draws on a wide range of academic approaches—political, social, cultural, and intellectual history, along with thumbnail biographies of major figures—and blends them deftly into a narrative that carries the reader along at a brisk pace., The tone of the book is scrupulously academic (with eighty pages of closely printed footnotes and bibliography).